Representative Genotyping, Recombination and Evolutionary Dynamics Analysis of TSA56 Gene Segment of Orientia tsutsugamushi - Jiali Long; Yuehong Wei; Xia Tao; Peng He; Jianmin Xu; Xinwei Wu; Wei Zhu; Kuncai Chen; Zhicong Yang (Frontiers in Cellular and Infection Microbiology, 2020)
Scrub typhus is a zoonotic disease caused by Orientia tsutsugamushi (O. tsutsugamushi). Orientia tsutsugamushi has various genotypes and more new strains with difference in sequences increasingly appeared. Whether the accurateness of one special nested PCR method which amplifies segment instead of entire open reading frame (ORF) sequence meets the current work of identifying new strains and classifying genotypes remains to be confirmed. And the origins and evolution of this organism have not been thoroughly elucidated. Accordingly, in this study, segments and the entire ORF of the 56-kDa type-specific antigen (TSA56) gene of O. tsutsugamushi were collected, including 209 clinically isolated strains in Guangzhou, China from 2012 to 2016 and 139 reference strains worldwide. By performing phylogenetic analysis, we proved that the accurateness of the particular PCR method which almost met detection need. This re-grouping result showed that segments perfectly represented and identified strains of Karp, Boryong, Gilliam, TA763, Kawasaki and part of Kato genotype, and this accuracy is not restricted by region and time. Sequence diversification of Shimokoshi and some Kato strains made their genotyping need to consider entire ORF sequences, but their weak recognition might not be due to recombination. The frequent genetic recombination and high point mutations contributed to genetic diversification of the TSA56 gene. Major overlapping regions of most recombination events occurred between strains of the same genotype, especially Karp and Kato genotype. And cross-genotype overlapping events occurred between Karp and Boryong/Gilliam/TA763/Kato, Kato and Kawasaki/Gilliam/TA686, Boryong and TA686, and Gilliam and Kawasaki. But Segment has quite low recombination frequency and stable mutation trend from 1943 to 2016. So segment is a relatively conserved part of the TSA56 ORF as for its stable trend of genetic diversity, and it may anchor and represent the entire TSA56 ORF gene. And genetic diversity is rejected as one potential reason for the increased incidence of scrub typhus. But an occasional recombination event created an unrecognized genotype which might be due to the breakage of VD II and AD II. Additionally, strains in Guangzhou were homologous and Karp genotype was detected as a dominant.